2021
DOI: 10.1016/j.ophtha.2020.06.028
|View full text |Cite|
|
Sign up to set email alerts
|

HAWK and HARRIER

Abstract: Purpose: To report the 96-week outcomes from HAWK and HARRIER. Design: Phase 3, prospective, randomized, double-masked, multicenter studies comparing efficacy and safety of brolucizumab 3 mg (HAWK only) and 6 mg with aflibercept 2 mg in eyes with neovascular age-related macular degeneration (nAMD).Participants: Treatment-naïve eyes with nAMD were randomized 1:1:1 to brolucizumab 3 mg (n ¼ 358), brolucizumab 6 mg (n ¼ 360), aflibercept 2 mg (n ¼ 360; HAWK) or 1:1 to brolucizumab 6 mg (n ¼ 370), aflibercept 2 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 255 publications
(51 citation statements)
references
References 17 publications
2
47
0
2
Order By: Relevance
“…Underlying cardiovascular disease (e.g., hypertension, diabetes mellitus, cardiac arrhythmia) may be a risk factor for BARV. All patients who experience occlusive vasculitis in the HARRIER and HAWK trials had underlying cardiovascular disease, and the same is true for the majority of patients in another retrospective case series [57,63]. Otherwise, no pattern of medical history, ocular history, or medication allergy has been identified [54,57,59,60].…”
Section: Epidemiology and Presentationmentioning
confidence: 87%
See 1 more Smart Citation
“…Underlying cardiovascular disease (e.g., hypertension, diabetes mellitus, cardiac arrhythmia) may be a risk factor for BARV. All patients who experience occlusive vasculitis in the HARRIER and HAWK trials had underlying cardiovascular disease, and the same is true for the majority of patients in another retrospective case series [57,63]. Otherwise, no pattern of medical history, ocular history, or medication allergy has been identified [54,57,59,60].…”
Section: Epidemiology and Presentationmentioning
confidence: 87%
“…Despite the Novartis safety committee's report, the exact incidence of BARV remains unknown. The expanded 96-week safety outcomes from the HAWK and HARRIER trials found that six of the 730 brolucizumab patients (0.8%) experienced intraocular inflammation-associated retinal artery occlusion or thrombosis [63]. A review of ASRS data indicated that 14 cases (11 of which were occlusive) had been voluntarily reported by providers out of the 46,000 brolucizumab injections that were administered in the United States to that date, suggesting an incidence of 3.0 cases per 10,000 injections [58] Similarly, post-market data from Novartis suggested the incidence of occlusive retinal vasculitis was 4.7 per 10,000 brolucizumab injections [64].…”
Section: Epidemiology and Presentationmentioning
confidence: 99%
“…The pivotal trials achieved their primary end point, with BCVA gains from baseline of +6.6 and +6.8 ETDRS letters (HAWK) and +6.9 and +7.6 ETDRS letters (HARRIER) with brolucizumab and aflibercept, respectively (Table 1). These vision gains were sustained up to week 96 in an analysis of the 2-year outcomes from the pivotal trials [30].…”
Section: Clinical Evidence Of Brolucizumab Usementioning
confidence: 99%
“…The superior reductions in CST from baseline observed with brolucizumab at week 16 were maintained at week 48 [7] and 96 [30], despite less frequent injections in the brolucizumab group. This is an important result, as variation in retinal thickness during anti-VEGF treatment was found to be associated with worse BCVA outcomes and the development of fibrosis in a recent analysis [13].…”
Section: Clinical Evidence Of Brolucizumab Usementioning
confidence: 99%
“…Later studies led to the approval of aflibercept, which has demonstrated non-inferiority to ranibizumab for most of these indications, with the exception of DME in which aflibercept showed better short-term visual outcomes in eyes with poor baseline vision (Heier et al, 2014;Korobelnik et al, 2014a,b;Clark et al, 2016). The most recently-approved brolucizumab is the smallest (28 kDa) in size, and may exhibit greater durability due to the higher achievable therapeutic molar dose, but may also trigger more intraocular inflammation that could limits its wide adoption (Baumal et al, 2020;Dugel et al, 2020). Other anti-angiogenic pharmacotherapies under investigation include pegylated anti-VEGF designed ankyrin repeat proteins (abicipar pegol), antibodies against Tie-2 receptor ligands (faricimab, nesvacumab, ARP-1536), and PDGF antagonists (ranucumab, X-82) (Shen et al, 2014;Frye et al, 2015;Callanan et al, 2018;Sahni et al, 2019;Cohen et al, 2020;Heier et al, 2020;Khanani et al, 2020).…”
Section: Current Treatments For Ocular Angiogenesismentioning
confidence: 99%